Sustentabilidade corporativa e combate ao greenwashing : análise da influência das normas e padrões internacionais no direito brasileiro - Censi, Guilherme (My University, 2026)
The increasing incorporation of sustainability discourse into corporate communication has heightened the risks of practices known as greenwashing, characterized by the disclosure of misleading, imprecise, and technically unfounded environmental information. In this context, given the significant incidence of greenwashing in the corporate sphere, this dissertation aims to examine how the Brazilian legal system, influenced by international sustainability standards, has regulated the disclosure of corporate sustainability information, assessing whether these normative developments are sufficient to prevent greenwashing and proposing pathways for improving Brazilian regulations. The research adopts a qualitative methodology of an exploratory and analytical nature, grounded in a literature review, normative analysis, and the examination of paradigmatic cases. The analysis demonstrates that, although the legal framework provides normative instruments capable of repressing greenwashing practices, weaknesses persist regarding the traceability, verifiability, and standardization of disclosed environmental claims, which undermines the effectiveness of legal protection and highlights the need to enhance normative and institutional mechanisms aimed at transparency and accountability in the disclosure of environmental information. [resumo fornecido pelo autor]
A crescente incorporação do discurso da sustentabilidade na comunicação corporativa tem ampliado os riscos de práticas conhecidas como greenwashing, caracterizadas pela divulgação de informações ambientais enganosas, imprecisas e desprovidas de respaldo técnico. Nesse contexto, a presente dissertação, diante da expressiva incidência de greenwashing no meio corporativo, objetiva examinar de que forma o ordenamento jurídico brasileiro, influenciado por padrões internacionais de sustentabilidade, vem regulando a divulgação de informações acerca de sustentabilidade corporativa, avaliando se esses avanços normativos são suficientes para a prevenção do greenwashing e propondo caminhos para o aperfeiçoamento das normas brasileiras. A pesquisa adota metodologia qualitativa, de caráter exploratório e analítico, fundamentada em revisão bibliográfica, análise normativa e exame de casos paradigmáticos. A análise evidencia que, embora o Direito disponha de instrumentos normativos aptos a reprimir práticas de greenwashing, persistem fragilidades relacionadas à rastreabilidade, verificabilidade e padronização das alegações ambientais divulgadas, o que compromete a efetividade da tutela jurídica e evidencia a necessidade de aprimoramento dos mecanismos normativos e institucionais voltados à transparência e à responsabilização na divulgação de informações ambientais. [resumo fornecido pelo autor]
Keywords: Direito ambiental - Brasil; Sustentabilidade - Aspectos jurídicos; Empresas - Aspectos ambientais; Publicidade enganosa - Aspectos ambientais; Environmental law - Brazil; Sustainability - Legal aspects; Fraudulent advertising - Environmental aspects; Business enterprises - Environmental aspects